Fear of Missing Out? A study of Indonesia’s Generation Z in Online Beauty Community - Valery Gunawan, Mary; Fakoniko , Cynthia Chrisnina (Cendekia Niaga, 2025)
Online Beauty Community provides brands and consumers with necessary apparatus benefit and to develop brandimage. This study investigates the influence of Online Consumer Brand Engagement (OCBE) on purchaseintention within the context of Indonesian Gen Z online beauty communities. It explores factors including Fear ofMissing Out (FOMO), Brand Involvement, and Online Brand Experience contribute to shaping OCBE, which inturn influences consumers' purchase intention of beauty products. Data analysis from 300 Gen Z participants inonline beauty communities reveals that these factors positively impact OCBE, ultimately leading to increasedpurchase intention. The findings confirm that FOMO, brand involvement, positive online experience, and OCBEall contribute to higher purchase intention. These insights can inform marketing strategies to drive consumerengagement and business growth. Furthermore, FOMO especially social aspects showed a stronger relationshipthan other factors that influence Online Consumer Brand Engagement. Therefore, Indonesian beauty industry canadopt pull strategy to make Gen Z consumers have the sense of FOMO in turns to increase their purchase intention.